Early Experiences with Studer’s Orthotopic Neobladder - Bhandari, Bharat Bahadur; Thapa, Bikash Bikram; Thapa, Narayan; Hamal, Bhairab Kumar (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Radical cystectomy and urinary diversion is the standard treatment option for muscle invasive urothelial carcinoma of urinary bladder. We analyzed the complications and functional outcome of 21 consecutive patients who underwent radical cystectomy and studer ileal neobladder substitution. Methods: This was a retrospective study from the review of chart and follow up details of 21 patients who underwent radical cystectomy and Studer ileal neobladder substitution from January 2009 to February 2014. Data obtained were the disease characteristics, both the early and late complications and urinary continence. Results: Total 21 patients were evaluated. 17 patients were available for follow up of one year or more. One patient died secondary to surgery related complications and 2 died due to exacerbation of comorbidities. And one patient lost follow up after one year. The rates of early and late morbidity were 33.3% (7) and 19% (4). Prolonged ileus developed in three patients and urinary tract infection was the most common among early and late complications (2, 8%). Two patients developed anastomotic stricture. Complete day time and night time continence was achieved in 82% (14) and 33.3% (7) respectively. The mean maximum neobladder capacity at end of one year was 345 ml. Conclusions: Outcome of studer’s ileal orhtotopic neobladder in our series is comparable with others. The result of our study is promising and encouraging to pursue it as a primary treatment option for muscle invasive and recurrent urothelial carcinoma of urinary bladder.